THE ROLE OF KNOWLEDGE MANAGEMENT ON THE RELATIONSHIP OF LEARNING ORGANISATIONS AND EMPLOYEES’ BEHAVIOR IN THAILAND’S HOTEL INDUSTRIES CRISIS - Sarun WIDTAYAKORNBUNDIT; Tanapoom ATIVETIN (Geo Journal of Tourism and Geosites, 2022)
The purpose of this study is to find solutions to the epidemic crisis by using knowledge management (KM) and learning organization (LO) to assess their work engagement and organizational commitment in employees. The sample group in this study is 392 management personnel in the hotel industry in Bangkok, Thailand. The study uses the quantitative research methodology and the structural equation model analysis. The results of the study revealed that KM has a direct influence on the intermediate variable, namely, LO, and an indirect effect on LO with a correlation to work engagement and organisational commitment (p < 0.05). The study represented almost variables has impact to each other. Human resource development could take into account the context and adapt the organization to be flexible and enthusiastic about learning amid changing circumstances, as well as understanding the condition of personnel in the organsation.